A Culture of Conspiracy: Apocalyptic Visions in Contemporary America - Barkun, Michael (Comparative studies in religion and society, 2013)
American society has changed dramatically since A Culture of Conspiracy was first published in 2001. In this revised and expanded edition, Michael Barkun delves deeper into America's conspiracy sub-culture, exploring the rise of 9/11 conspiracy theories, the ""birther"" controversy surrounding Barack Obama's American citizenship, and how the conspiracy landscape has changed with the rise of the Internet and other new media. What do UFO believers, Christian millennialists, and right-wing conspiracy theorists have in common? According to Michael Barkun in this fascinating yet d